2002
DOI: 10.1089/10430340252769761
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance 1 Gene Transfer Can Confer Chemoprotection to Human Peripheral Blood Progenitor Cells Engrafted in Immunodeficient Mice

Abstract: Myelosuppression is the main side effect of cancer chemotherapy. An improved rate of retroviral vector-mediated gene transfer to hematopoietic stem cells, shown in more recent clinical trials, has created the basis to test the concept of myeloprotective gene therapy. We transplanted clinical-scale human peripheral blood progenitor cell grafts (n = 2) transduced with retroviral vector SF91m3, which contains the human multidrug resistance 1 gene (MDR1), into nonobese diabetic/severe combined immunodeficient (NOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…A high level of engraftment of these cells in the BM of NOD/SCID mice ( Table 2) and gene transfer levels equivalent to recent clinical 10 or myeloprotective experimental trials 33 with this transgene were found. Our data suggest that approximately one vector copy integration had occurred per MDR1-transduced SRC, which can be estimated from the gene transfer frequency (mean, 17.6%, Table 2), the transgene expression (mean, 8.5%) and an additional proportion of nonfunctional splice variants of the wild-type MDR1 transgene used here.…”
Section: Discussionmentioning
confidence: 59%
“…A high level of engraftment of these cells in the BM of NOD/SCID mice ( Table 2) and gene transfer levels equivalent to recent clinical 10 or myeloprotective experimental trials 33 with this transgene were found. Our data suggest that approximately one vector copy integration had occurred per MDR1-transduced SRC, which can be estimated from the gene transfer frequency (mean, 17.6%, Table 2), the transgene expression (mean, 8.5%) and an additional proportion of nonfunctional splice variants of the wild-type MDR1 transgene used here.…”
Section: Discussionmentioning
confidence: 59%
“…37 For multiple myeloma it could be shown that purged vs un-purged transplants did not result in different disease free or overall survival, suggesting that transplanted tumor cells did not significantly contribute to tumor relapse. 37 The most intense studied genes for chemoprotective gene therapy are MDR1 [6][7][8][9][10] and MGMT. [24][25][26] As drug combinations are common in most chemotherapeutic regimens, gene therapy with a combination of several genes is particularly promising and would increase the therapeutic index of combination chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Previous findings of our group for the first time indicated that an optimized retroviral vector and transduction protocol resulted in clinically relevant levels of MDR1 gene marking and expression, as well as in chemoprotection of human hematopoiesis in vivo in a NOD/SCID mouse xenotransplantation model. 6 Recently, MDR1 expressing vectors have already been validated in clinical trials for the feasibility of bone-marrow chemoprotection. [7][8][9][10] Chemoresistance conferred by the human MGMT is based on a different mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Various attempts were shown for chemoprotection of HSCs by retroviral transfer of MDR1 or MGMT. Gammaretroviral transfer of MDR1 into murine HSCs resulted in efficient chemoprotection against paclitaxel 13 or taxol. [14][15][16] These promising results could not be repeated in marmosets or dogs treated either with paclitaxel 17 or docetaxel.…”
Section: Introductionmentioning
confidence: 99%